Treatment of Common Femoral Artery Pseudoaneurysm: A Novel Approach Utilizing a VASCADE Percutaneous Closure Device - Mark Dalvin; Brandon Dessecker; Eugene Vitvitsky (Case Reports in Surgery)
Iatrogenic common femoral artery pseudoaneurysm is a well-known complication to vascular access. Many options, both surgical and nonsurgical, have been implemented as means to treat pseudoaneurysms such as thrombin injection, image-guided compression, and percutaneous closure devices. This case report demonstrates a novel technique using a VASCADE closure device to successfully treat an iatrogenic common femoral pseudoaneurysm.